2022
DOI: 10.3389/fphys.2021.814542
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Rate Change Differences in QT/RR Hysteresis in Healthy Subjects

Abstract: While it is now well-understood that the extent of QT interval changes due to underlying heart rate differences (i.e., the QT/RR adaptation) needs to be distinguished from the speed with which the QT interval reacts to heart rate changes (i.e., the so-called QT/RR hysteresis), gaps still exist in the physiologic understanding of QT/RR hysteresis processes. This study was designed to address the questions of whether the speed of QT adaptation to heart rate changes is driven by time or by number of cardiac cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…It was found that the rate of QT/RR hysteresis decreases with increasing age, while the duration of the individually corrected QTc interval increases with increasing age. In contrast to longer QTc intervals, the rate of QT/RR hysteresis was faster in women [145]. There are many causes of prolonged QT intervals, and acquired causes are more common than genetic causes [146].…”
Section: Qt Interval Duration (Ms) Under Individual Types Of Anesthes...mentioning
confidence: 84%
“…It was found that the rate of QT/RR hysteresis decreases with increasing age, while the duration of the individually corrected QTc interval increases with increasing age. In contrast to longer QTc intervals, the rate of QT/RR hysteresis was faster in women [145]. There are many causes of prolonged QT intervals, and acquired causes are more common than genetic causes [146].…”
Section: Qt Interval Duration (Ms) Under Individual Types Of Anesthes...mentioning
confidence: 84%
“…In other studies, autonomic blockades were used to assess QT hysteresis during exercise and recovery, providing evidence on the important role of autonomic nervous system effects on the QT-to-RR relationship [ 59 ]. Nevertheless, subsequent reports pointed out that the conclusions of those studies might be influenced by factors like the speed of HR change, which is also subjected to autonomic influence [ 69 ]. Here, we aimed to shed light on the role of β -adrenergic stimulation on the APD and QT adaptation lag after HR changes separately during exercise and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The ECG recordings used in the study have been reported previously in studies that investigated very different electrophysiology factors ( Hnatkova et al, 2021 ; Andršová et al, 2022 ; Toman et al, 2022 ). For the purposes of the present investigation, we applied very different data processing methods.…”
Section: Methodsmentioning
confidence: 99%
“…The expressions of underlying heart rate based on a simple average of preceding RR intervals does not reflect gradual decrease of the influence of heart rate changes in more remote history. Therefore, exponential decay models were also used, in the same form as previously developed for the purposes of estimating QT/RR hysteresis ( Malik et al, 2008b ; Malik et al, 2016 ; Andršová et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation